EFFECT OF SEED PRIMING ON CROP GROWTH AND SEED YIELD OF SOYBEAN [GLYCINE MAX (L.) MERILL] - RAHUL B. AGAWANE; SACHIN D. PARHE (The Bioscan, 2015)
The results exhibited that seeds primed with GA3 @ 100 ppm (T4), 0.5 % KNO3 (T5) recorded significantly higher germination percentage i.e. 87.33%) and 87.00 % respectively over the untreated control T1(83.00%). The treatments (T4) GA3 100 ppm 12 hr (77.19), (T8) Hydration with IAA @ 80 ppm 12hr (76.55) and (T3) Hydration with CaCl2 (2.0%) 12 hr (76.22) maintained the optimum plant stand at harvest over untreated control (T1). This may likely contributed for boosting up economic yield in soybean cultivar, JS- 9305. The seed priming significantly influenced the seed yield and yield contributing characters of soybean. The seed priming treatments (T4) GA3 100 ppm 12 hr, (T7) hydration with water + Bavistin 3.0 g/kg found effective for improvement in dry matter content of seedling (g) in soybean variety JS- 9305. The treatments (T4) 100 ppm GA3 12 hr (2078.00 g/plot), (T8) hydration with IAA 80 ppm 12 hr (2008.67 g/plot), (T5) Hydration with 0.5 per cent KNO3 12 hr (1991.00g/plant) seed yield per plot respectively over the untreated control T1 (1647.67g/plot) showing to the corresponding favourable improvement in number of pods per plant, number of seeds per pod, test weight (g), seed yield per plot (gm), seed yield per Ha (q), biological yield (g) and numerical harvest index (%).